Bacterial Communities Nodulating Lupinus cosentinii Gus. and Their Inputs in the Worldwide Phylogeography of Lupine Endosymbionts - Mokhtar Rejili; Mohamed Ali Benabderrahim; Mohamed Mars (Soil Systems, 2024)
Genetic variability in bacterial populations that nodulate Lupinus cosentinii in Tunisia was investigated. Phylogenetic studies of 40 isolates using recA partial sequences categorized them into three clusters within the Bradyrhizobium genus. Twenty-three strains selected from the three clusters were thoroughly examined through housekeeping genes (recA, glnII and rpoB) multilocus sequence analysis (MLSA). Our results showed that 23 representative strains were distributed in five distinct clusters, with 13 strains belonging to Bradyrhizobium canariense BTA-1T/Bradyrhizobium lupini USDA3051T (10 strains) and Bradyrhizobium hipponense aSej3T (three strains) lineages. Interestingly, eight strains occupied a separate position and could belong to two putative novel Bradyrhizobium species. The nodC phylogeny placed the 23 strains within three symbiovars: genistearum (19 strains), lupini (two strains) and, for the first time, the symbiovar cyanophyllae (two strains). Based on the worldwide phylogeography of rhizobial symbionts nodulating lupine (14 species), our results reported that eight species occurred in more than one continent, and six species were specific for one continent, e.g., Bradyrhizobium rifense, Bradyrhizobium diazoefficiens, Phyllobacterium sp. and Devosia sp. were specific to the African continent, the Bradyrhizobium iriomotense/Bradyrhizobium stylosanthis group to America, and Bradyrhizobium valentinum to the European continent.